Effectiveness Test of Soursop Leaf Extract and Papaya Leaf Extract Combination Against Spodoptera litura on Chili Plants in Tobelo City - Nonice Manikome; Morina Handayani (Agrikan: Jurnal Agribisnis Perikanan, 2020)
In terms of control, various natural chemical compounds derived from plants can be used. Like papaya and soursop leaves, the formulation of the problem is whether the combination of soursop leaf extract and papaya leaf extract is effective in controlling S. litura pests and what is the most effective extract concentration. This study used a completely randomized design (RBD) with 5 treatments and 5 replications. Observation variables included symptoms, morphological changes and mortality, the results were analyzed by Analysis of Variance (ANOVA) followed by the Least Significant Difference (LSD) 5% test. The initial symptoms that were seen one day after application of the combination were morphological changes in the test larvae. Such as damage to the body of the larva, change in color, then the larva's body shrinks, when touched the larvae easily fall. The highest mortality was found at the extract concentration of 20% with a mortality rate of 64.79% on the second day. The results showed that the high mortality rate was closely related to the high toxicity contained in the 20% extract concentration. It was concluded that the results of the effectiveness test of the combination of papaya leaf extract and soursop leaf extract were effective. Suggestions for the use of natural materials that are easily available can be used as an alternative to control pests that are environmentally friendly. Furthermore, it is suggested that if you want to increase mortality, you can try increasing the extract concentration.